2017
DOI: 10.1097/hnp.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reiki on Pain, Anxiety, and Blood Pressure in Patients Undergoing Knee Replacement

Abstract: This blinded, controlled pilot study investigated the effects of Reiki on 46 patients undergoing knee replacement surgery. Of the 3 groups, Reiki, Sham Reiki, and Standard of Care, only the Reiki group showed significant reductions in pain, blood pressure, respiration rate, and state anxiety, which provides evidence for a full-scale clinical study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(118 citation statements)
references
References 4 publications
2
57
0
6
Order By: Relevance
“…Therefore, individuals with health concerns corresponding with the aforementioned symptoms may show the most promise for treating with Reiki. Indeed, the results of this nonclinical real-world study are consistent with small sample clinical trials in which Reiki was associated with improvements in well-being [16][17][18][19][20][21] and alleviation of pain, 3,22-24 emotional stress, [25][26][27][28] anxiety, 21,23,26,28 and depression. 25,29 Positive affect was below norm levels at pre and increased to norm levels at post, whereas negative affect was at norm and decreased to below norm levels following Reiki.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, individuals with health concerns corresponding with the aforementioned symptoms may show the most promise for treating with Reiki. Indeed, the results of this nonclinical real-world study are consistent with small sample clinical trials in which Reiki was associated with improvements in well-being [16][17][18][19][20][21] and alleviation of pain, 3,22-24 emotional stress, [25][26][27][28] anxiety, 21,23,26,28 and depression. 25,29 Positive affect was below norm levels at pre and increased to norm levels at post, whereas negative affect was at norm and decreased to below norm levels following Reiki.…”
Section: Discussionsupporting
confidence: 80%
“…Reiki is notably classed in the category of biofield energy therapy by the National Center for Complementary and Alternative Medicine 6. In 2007, a USA Today article reported that 15% of hospitals in the USA (>800) offer Reiki therapy as a regular part of patient services 7 8. Reiki is also officially recommended by the National Health Service Trusts and The Prince of Wales’s Foundation for Integrated Health in the UK.…”
Section: Reiki: Definition and Historymentioning
confidence: 99%
“…Searches identified 4898 articles, and 781 full-text articles were assessed for eligibility. Twelve RCTs with a total of 1299 participants were eligible for inclusion 35–46. A PRISMA flow diagram is provided in figure 1.…”
Section: Resultsmentioning
confidence: 99%